Extrapolation-Based Acceleration of Iterative Solvers: Application to Simulation of 3D Flows (Communications in Computational Physics, 2011)
We investigate the effectiveness of two extrapolation-based methods aimingto approximate the initial state required by an iterative solver in simulations of unsteadyflow problems. The methods lead to about a ten-fold reduction in the iterationcount while requiring only negligible computational overhead. They are particularlysuitable for parallel computing since they are based almost exclusively on data storedlocally on each processor. Performance has been evaluated in simulations of turbulentflow in a stenosed carotid artery and also in laminar flow in a very large domaincontaining the human intracranial arterial tree.